Aktivitas Antibakteri Ekstrak Daun Mangrove (Rhizophora mucronata) pada Bakteri Helicobacter pylori Penyebab Tukak Lambung - Reza Pertiwi; Salprima Yudha S; Risky Hadi Wibowo; Doni Notriawan; Riski Padilah Nasution; Afra Wafiqah Azhar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Mangrove (Rhizophora mucronata) is a plant that can be used as an antibacterial because it contains several secondary metabolite compounds such as saponins and flavonoids which can inhibit bacterial growth. This research aims to determinehe antibacterial activity of mangrove leaves (Rhizophora mucronata) in inhibiting the growth of Helicobacter pylori bacteria. This research is an in vitro study using the agar dilution method for 2-5 days. The treatment groups consisted of negative, positive (co-trimoxazole), ethanol extract of mangrove leaves (Rhizophora mucronata) with concentrations of6.25%, 12.5%, 25% and 50%. The treatment was carried out by adding the Helicobacter pylori suspension to a petri dish containing agar media. Observations were made to see whether bacteria grew in the media. The data is then analyzed and broken down from the results of calculating the diameter of the inhibition zone. The test results showed that the ethanol extract of mangrove leaves (Rhizophora mucronata) had antibacterial activity in the weak category in inhibiting the growth of Helicobacter pylori bacteria. This antibacterial activity can be caused because mangrove leaves (Rhizophora mucronata) contain secondary metabolite compounds with an antibacterial mechanism of action, so this is in line with the results of this study.